Ein Kranz Mercator zu Ehren - de Waele, Ferdinand Jozef (ERDKUNDE, 1962)
He was born on March the 5th, 1512, at Rupelmonde in Eastern Flanders and died in Duisburg on the 2nd Decem ber, 1594 - largescale joint Germano-Belgian celebrations took place in Antwerp, Rupelmonde and Sint Niklaas Waas on April 4th and in Duisburg on September 8-9th, 1962. In Duisburg an exhibition “Mercator and his time was prepared by Professor Fritz Tischler in the Lower Rhenish Museum in Duisburg. It was oponed with a lecture from Professor Ferdinind Josef De Waele (Ghent) entitled “A tribute to Mercator. On the Occasion of the academic celebration at a meeting in the Mercator Hall Professor Carl Troll (Bonn) spoke on “The history and importance of geography at the present day. Professor De Waele's lecture appears below.